Probes Vacillating and Mapping Technique at Testing Micro-area Sheet Resistance - Zhihui Zhu; Xinfu Liu; Runli Zhang; Ruqing Zhang; Nan Jiang (Institute of Advanced Engineering and Science, 2013)
This article briefly elaborated the basic concepts of the probe vacillated at testing a large silicon wafer with square four point probe equipment. The importance of the micro-area’s sheet resistance is discussed and the basic principles of four point probe measurement technology are analyzed. Some factors that affect the measurement accuracy are studied, and interference can be avoided while measuring and analyzing the impact on square four point probe measurement by probe vacillate. The calculation formula of the square micro-area probe measurement is deduced when probes vacillated discretionarily. An experiment was made with a small wafer sample and accurate resistivity was gotten. The electrical resistivity is tested for another silicon wafer by a square four point probe equipment. Color Mapping graphics was designed for displaying the micro-area resistance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2338